Expression of the BAX Gene, CO1 Gene, and their Relationship to the Motility and Spermatozoa Concentration of Rats Treated with Moringa oleifera Leaf Extract - Hasanah, Uswatun; Fauziah, Cut; Irsyad, Nasihin saud; Pramono, Andri Pramesyanti; Wahab, Dinda Hanifah; Nawawi, Wafa Nabila (HAYATI Journal of Biosciences, 2025)
Spermatogenesis is the process of spermatozoa formation. An increase in free radicals, such as in hyperglycemia conditions, causes oxidative stress, which can interfere with spermatogenesis. Oxidative stress is an inequality condition between the body’s capacity to produce antioxidants and the rise of free radicals. Antioxidants such as flavonoids are contained in plants such as Moringa oleifera leaves. During spermatogenesis, an apoptosis process involves the BAX gene. BAX is a gene that functions as pro-apoptosis. There is also a CO1 gene in mitochondria, which plays a role in cellular metabolism. Gene expression examination assesses the comparative threshold cycle (CT) with RT-PCR, and spermatozoa quality examination includes assessing spermatozoa concentration and motility. This study used 30 male white Sprague Dawley rats as the test animals, which were divided into five treatment groups: treatment of moringa leaf extract dose 200 mg/kg BW, treatment dose 300 mg/kg BW, treatment dose 400 mg/kg BW, normal control group, and positive control group. The results showed a decrease in BAX gene expression and CO1 gene expression in the treatment group of test animals. The results of sperm analysis showed an increase in spermatozoa concentration in all treatment groups compared to the control group. For sperm motility in the 400 mg/KgBB dose treatment, an increase in sperm motility compared to the control group. This study concludes that administering moringa leaf extract reduced the expression of the Bax and CO1 genes. However, no significant changes were observed in sperm concentration and motility within the treatment group.